Perancangan, Pembuatan, dan Pengujian Pembangkit Listrik Energi Biomassa - Rachmat Cahaya Putra; Indra Mamad Gandidi; Harmen Burhanuddin (Jurnal Ilmiah Teknik Mesin, 2013)
This paper describe about designing and testing laboratory-scalebiomass energy power plant, toprovideelectricityin remote areasand islandswhich utilizerenewable energyin accordancewith thepresident decreeNo.5/2006. The power plantis built with gasificationreactorwhich designedbased onImbertdowndraftgasifier, integrated gas cleaned up system (IGCS) include cyclones, venturiscrubbersrectangulartype, and a new gas cleaner which called rotaryseparator. Experiments carried out withthe parametersof gasificationsystemsAFR0.48,0.5, 0.54,scrubbingwater flow 1.26, 2.62, 3.33l/min, rotaryseparator suction speed about 0.9,3.4,4.4 m/s. Each of parameters was interacted to producecleanproducer gas which free from tarandimpurities, as wellas ahigh calorificvalue as fuelgasgenerator. The result of experiment and literature review shows thatthecurrentgasificationAFR about 0.54still far enough from ideal rice husk gasification AFRabout 1.5. Eventhough, the remaining taris stillrelativelyhigh at3788.1mg/m3. AfterIGCSinstalled,the tarcan be significantly reducedto210.45mg/m3, with thescrubbingwater flow3.33l/min, and4.4 m/s suction speed of rotaryseparator. In addition, theelectric powergeneratedis stillbelow 100W,so installationshouldbe modifiedagain, especially in thesector ofair supply tothe reactor.Keywords : electricity crisis, biomass gasification, biomass energy power plant.